2018
DOI: 10.1021/acs.energyfuels.7b03588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Representation of the Petroleum Gasoline Fraction

Abstract: The computer-aided reconstruction of gasoline composition is an active area of petroleum and petrochemical research as a result of the demand for molecular-level management of the petroleum feed streams. To that end, in this work, a molecular compositional model based on a predefined representative molecular set was built that allows for the conversion of conventional bulk property data to an approximate molecular composition. The selection of representative molecules was based on their presence in gasoline mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Naphtha belongs to the light oil group; it contains up to 400 species. 26 Although naphtha can be represented by these prespecified molecules, it is still hard to identify the contents of all these 400 components. Research works are focused on reducing the number of prespecified molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naphtha belongs to the light oil group; it contains up to 400 species. 26 Although naphtha can be represented by these prespecified molecules, it is still hard to identify the contents of all these 400 components. Research works are focused on reducing the number of prespecified molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the prediction of this method is effective. Cui et al 26 proposed a library containing 89 hydrocarbons and 81 heteroatom-containing species in their molecular representation of the petroleum gasoline fraction. They introduced a gamma probability density function instead of the entropy maximization to regulate the content relations between components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from the graphs, the distribution within each homologous group (paraffins, iso-paraffins, olefins, naphthenes, and aromatics) did not statistically obey any distribution function. This made it impossible to apply known models [9,[47][48][49][50] based on the assumption of a change in composition in accordance with the known statistical distribution within the homologous group. The unevenness in the composition of raw materials and distribution by homologous groups can also be seen.…”
Section: Statistical Descriptive Analysis Of the Samplesmentioning
confidence: 99%
“…(5) High cost of equipment for the study of these processes, etc. However, taking into account these issues, the use of APC algorithms along with technological developments will certainly increase the efficiency of secondary oil refining processes, as well as bring additional profit to oil refineries [9,10]. Although advanced control systems are based upon mathematical models, it is difficult to obtain accurate mathematical models describing a process in petroleum or a related field [11].…”
Section: Introductionmentioning
confidence: 99%